Challenges and Opportunities for Using Information Technology in Online Learning During Covid-19 - Twagiramungu, Protais (Jayapangus Press, 2023)
This research was conducted to determine the challenges and opportunities of using information technology in online learning at Groupe Scolaire de Butare during the Covid-19 pandemic using library study and survey methods. The sample used in this research was all students of Groupe Scolaire de Butare Semester I and Semester II. The Covid-19 pandemic has had an impact on universities in Rwanda, with the implementation of a physical distancing policy which then became the basis for holding online lectures using information technology. The media most widely used in online learning at Groupe Scolaire de Butare are WhatsApp and Google Classroom because this application is very easy to use. However, there are several obstacles such as lack of facilities. Based on survey results, 50% of students do not have laptops, and 80% of students have difficulty getting a signal and are wasteful in using data plans because many students live far from urban areas. This research was ineffective because 61.5% of students stated that they had never used online learning media before the COVID-19 pandemic. However, the fact that using online learning has triggered the acceleration of the digital transformation process of Rwandan education. Before the pandemic, several discourses, supporting policies and outreach regarding the education era 4.0 were unsuccessful. However, Covid-19 has tremendously impacted digital transformation towards the education era 4.0.